Morphosyntactic analysis of PSAU BS Agriculture first year students’ written compositions - Rodolfo P. Dizon Jr; Jamayma M. Gatchalian (Journal of Education, Social & Communication Studies, 2025)
In today’s world, the ability to compose sentences that adhere with the Standard American English has been a concern in many academic institutions. Despite the effort of helping students, problems still arise as congruent with the findings of Seli, et al (2021) where students show confusion in differentiating a noun phrase from an adjective phrase. Using corpus linguistics, this study attempted to analyse the morphosyntactic features of the randomly selected First Year BS Agriculture students’ written compositions. Data was collected from the readily-available outputs in Purposive Communication during their writing topic.  As main research frameworks, the study employed Yule’s (2010) Morphological Analysis and Morley’s (2006) Syntactic Analysis in order to gather the necessary data. Regarding the syntactic features, the analysis revealed that verb tenses, subject-verb agreement, and prepositions deviate the most from Standard American English. Meanwhile, in the morphological analysis, these types of errors were seen in the writings of the students: singular/plural nouns and pronouns, articles, conjunctions, and using other parts of speech. Based on these deviations, work plan for an extension activity may be designed and implemented to address issues. In addition, the locale of the current study, participants have only one English subject making; thus, writing as a separate subject should be included in the General Education curriculum.